Social Marketing Communication in Fostering Local Community Acceptance of Tourism Village Development: A Case Study of Gampong Nusa, Aceh - Uswatun Nisa; Novi Susilawati; Desi Maulida; Novita Sari; Safrida; Rachmatika Lestari (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Purpose − This study examines how social marketing communication strategies were used by the Nusa Tourism Institute (Lembaga Pariwisata Nusa) to build community acceptance toward the development of Nusa Tourism Village in Aceh Besar. The transformation of Nusa from a conventional rural settlement into a community based tourism destination did not occur quickly. Early reactions were marked by strong resistance driven by concerns over cultural change, religious norms, and stereotypes about visitors. Method − Using a qualitative case study approach, this research explored the process through which community attitudes shifted from rejection to acceptance and eventually to active participation. Data were collected through in depth interviews with local leaders, LPN administrators, UMKM actors, and residents Findings − The findings show that acceptance emerged through a gradual communication process shaped by the components of the 7P social marketing mix. LPN introduced community based halal tourism as the core idea, built positive perceptions through education and demonstration, and used social media to display observable benefits. These stages of change align with the Theory of Planned Behavior, where attitudes, subjective norms, and perceived behavioral control strengthened in parallel until residents felt confident and capable of participating. The study concludes that culturally sensitive social marketing can reduce social resistance and support the development of sustainable community based tourism.